PENERAPAN LEAN MANUFACTURING UNTUK MENGURANGI PEMBOROSAN PADA UNIT PRODUKSI CV. ABC - Hanan Afifah Rachmadini, (2022)
CV. ABC is one of the companies engaged in the printing sector which was founded in 2017. CV. ABC serves various kinds of orders such as product front stickers, tool specification stickers, product information stickers, barcode stickers and others. However, in the production process CV. ABC found that there was waste that could cause the production process to be ineffective and efficient and reduce productivity. This study aims to identify and overcome waste problems through the provision of improvement proposals in the form of a production system design to increase efficiency and effectiveness through a Lean Manufacturing approach and simulation methods. The method used starts from Questionnaire 7 Waste, Value Stream Analysis Tools, Value Stream Mapping, Process Activity Mapping, Failure Mode Effect Analysis, Fishbone Chart and continues with simulation design using ProModel Software. The results showed that with the recommendations for improvement that have been proposed can reduce production time on CV. ABC from 15060.29 seconds to 13363.49 seconds. In addition, the total production in the simulation improvement results increased by 30.48%.